Manajemen Asuhan Kebidanan Komprehensif Pada Ny ”S” dengan Nyeri Punggung di Wilayah Kerja Puskesmas Lasepang Kabupaten Bantaeng: Management of Comprehensive Midwifery Care for Mrs "S" with Back Pain in the Work Area of ​​the Lasepang Health Center, Bantaeng Regency - Sumarni; Nurul Hidayah; Haerani (Jurnal Midwifery, 2023)
Introduction Comprehensive midwifery care is midwifery care starting from pregnancy, childbirth, postpartum, newborn and family planning. Care provided as a form of implementing midwives' functions, activities and responsibilities in providing services is one of the efforts to reduce MMR and IMR in Indonesia, especially in Bantaeng district, Lasepang Health Center. Method used are interviews, observations, physical examinations, supporting examinations, literature studies and documentation studies. Result At K1 Pregnancy Care, there were complaints from mothers, namely back pain, care given to overcome maternal problems, namely Prenatal yoga. And on KN 2 the mother has no complaints. At Mrs “S” delivery care, 60 APN steps were carried out normally and did not experience complications, bleeding ± 150 cc, uterine contractions were good. In BBL care the baby was born spontaneously at term and according to gestational age, male with an Apgar score of 8/10, with a birth weight of 3,600 grams. On KN 2 there are no complaints. On KF 1 and 2 the mother had no complaints. In KB care Mrs "S" became a acceptor of KB implants Conclusion there are no problems/abnormalities with Mrs "S" starting from pregnancy care, childbirth, babies, postpartum and family planning related to this, Mrs "S" is categorized in a normal/physiological state